TEACHER CHARACTER; TASAWWUF’S PERSPECTIVE - Zailani, Zailani (Proceeding International Seminar of Islamic Studies, 2023)
Abstract This article is titled Teacher Character; Tasawwuf’s Perspective. Articles discuss This article discusses what character a teacher must have and what a teacher does before and after starting teaching at school and how the teacher behaves when he meets his students at school. The method used in this article is a qualitative approach to library research. The sources used are books and literature related to the study under study. The result is that, before the teacher starts the learning process and during the learning period, the teacher does psychological exercises ordered by Allah. The exercises include Tahajjud prayer, reading the Qur'an, and reciting. There are several times that are used in maintaining a relationship with God, including before sunrise, before sunset, at midnight, and at the end of the day. The time and practise commanded by Allah have a good influence on a person's ability to carry out his duties as an educator. The teacher also carries out the 3S concept, namely: greetings, greetings, and smiles. Greetings are carried out between teachers and students, teachers with teachers, and students with students, as well as greetings and smiles.